Industry 4.0: digital twins characteristics, applications, and challenges in-built environments - Heni Zribi; Taycir Ben Abid; Abdelkarim Elloumi; Yasmina Hani; Besma Bechir Graba; Aderrahman Elmhamedi (Production and Manufacturing Research: An Open Access Journal)
The emergence of Digital Twins (DT) represents a significant technological innovation aimed at enhancing the design, construction, and operation of built assets. DT are virtual representations of physical objects, allowing an effective management across various stages within the construction and infrastructure sectors. While DT technology offers considerable potential, it remains in its infancy and faces challenges such as integration with other Industry 4.0 technologies and uncertainties about their actual uses and applications still exist. This paper seeks to define and explore the key characteristics of DT within the built environment, examine their relationship with Building Information Modeling (BIM), and evaluate their interactions with other Industry 4.0 technologies in the construction and maintenance of assets. Despite these potential benefits, several challenges prevent the widespread adoption of DT technology such as data security and ownership concerns, the lack of common data standards and interoperability, and difficulties in managing diverse source systems.